Determinants of capital structure of listed firms in Vietnam: A quantile regression approach - Nguyen, Thi Canh (University of Economics Ho Chi Minh City, 2023)
This study empirically examines the link between firm characteristics and leverage using the data of Vietnamese non-financial listed firms from 2006 to 2015. In addition to traditional panel data methods, we employ a conditional quantile regression that unveils the behavior of regressors throughout the leverage distribution. The results confirm the non-linear relationship between firm characteristics and leverage at different levels of debt.